Product Legality as a Legal Protection Effort for UMKM Industrial Brands in Indonesia - Larasati, Tengku Indira (PT. Anagata Sembagi Education, 2024)
This research aims to investigate the role of product legality as an effort to legally protect the brands of the MSME industry in Indonesia. MSMEs play an important role in the Indonesian economy, but often face challenges in protecting their brands. Product legality is an important aspect in protecting MSME brands. The research method used is descriptive by collecting data from related literature and primary sources. The findings show that having products that have clear legality can provide stronger legal protection for MSME brands. A legal trademark registration process that complies with regulations can increase consumer trust, strengthen brand reputation, and reduce the risk of brand infringement. However, challenges such as high costs, complexity of the registration process, and lack of understanding of the importance of product legality are still obstacles for MSMEs. Therefore, there needs to be efforts from the government, non-government organizations and other related parties to provide support and resources to MSMEs in understanding and fulfilling product legality requirements.